The Implementation of Principal Policies and the Role of Teachers in Fostering Students' Environmental Awareness through the Kurasaki Habit at Cibadak 05 Public Elementary School - Putri Raudhah Herros; M Syadeli Hanafi; Isti Rusdiyani (Yayasan Payungi Smart Madani, 2025)
This study explores the implementation of school principal policies and the role of teachers in fostering students’ environmental awareness through the KURASAKI (Clean Friday Movement) program at SDN Cibadak 05, Tangerang Regency. Employing a qualitative approach, data were collected through observations, interviews, and document analysis. The results indicate that the principal plays a strategic role in initiating policy, establishing an implementation team, and overseeing program execution. Meanwhile, teachers serve as facilitators and role models, actively guiding students in cultivating environmentally responsible behavior through daily routines and practical involvement. The study identifies key challenges, including limited student awareness and inadequate waste management infrastructure. In response, the school has enhanced socialization efforts and improved supporting facilities. The KURASAKI program has been effective in increasing students' environmental awareness and has significantly contributed to creating a cleaner, healthier school environment. As a result, students demonstrate a deeper understanding of environmental stewardship and are able to practice the KURASAKI habits more consistently and effectively. This study contributes to the field of environmental education by illustrating a practical school-based model that integrates leadership policy and teacher engagement to instill sustainable habits in students. It offers valuable insights for other schools aiming to implement similar environmental programs, emphasizing the importance of collaborative efforts, structured routines, and ongoing support to foster lasting behavioral change among learners.